Smart technology : first International Conference, MTYMEX 2017, Monterrey, Mexico, May 24-26, 2017, Proceedings /: first International Conference, MTYMEX 2017, Monterrey, Mexico, May 24-26, 2017, Proceedings. (2018) - Unknown
No abstract available